E-cigarette smoking: Awareness, use, and perceptions of Vietnamese personnel - Thoai Dang Nguyen; Hien Thi Bich Tran; Hieu Thi Thanh Nguyen; Dat Thanh Ha (GarVal Editorial Ltda., 2022)
Context: Electronic cigarettes (e-cigarettes) are considerably popular, particularly among young adults. Their effects have elicited strong interest in cigarette control and community health, but evidence on the knowledge, usage, and perceptions of e-cigarettes among the Vietnamese population remains limited. Aims: To evaluate e-cigarette awareness, use, and perceptions among Vietnamese personnel. Methods: A cross-sectional study through an online survey was administered to 368 participants in March 2022. The questionnaire comprised sections on socio-demographic characteristics and awareness, use, sources of information, and perceptions of e-cigarettes. Results: Most of the participants were male (87.8%), married (65.2%), and living in urban areas (77.2%). Their average age was 34.6 ± 16.1 years. 56.8% had never smoked, 23.9% were smokers, and 19.3% used to smoke. There was low awareness of e-cigarettes with 26.1%, whereas 8.2% were using e-cigarettes. Most respondents (86.5%) accessed the Internet for e-cigarette information, followed by television or radio (54.2%). Although over half of the respondents who heard about e-cigarettes expressed positive attitudes toward the cost and safety of e-cigarettes compared with traditional equivalents, they remained uncertain concerning their effectiveness in advancing smoking cessation. Statistically significant differences (p<0.05) in e-cigarette awareness and use were found between the respondents depending on gender, marital status, residence, and education. Conclusions: Our findings could guide the development of public health plans and national policies on e-cigarette control. Future studies should determine the permanent effects of e-cigarettes on community health and society.